Identification of Reversible Disruption of the Human Blood-Brain Barrier following Acute Ischemia - Simpkins, Alexis N. (Stroke, 2016)
BACKGROUND & PURPOSE: Animal models of acute cerebral ischemia have demonstrated that diffuse blood-brain barrier (BBB) disruption can be reversible following early reperfusion. However, irreversible, focal BBB disruption in humans is associated with hemorrhagic transformation in patients receiving intravenous thrombolytic therapy. The goal of this study was to use an MRI biomarker of BBB permeability to differentiate these two forms of BBB disruption. METHODS: Acute stroke patients imaged with MRI prior to, 2 hours after, and 24 hours after treatment with IV tPA were included. The average BBB permeability of the acute ischemic region before and 2 hours after treatment was calculated using a T2* perfusion-weighted source images. Change in average permeability was compared with percent reperfusion using linear regression. Focal regions of maximal BBB permeability from the pre-treatment MRI were compared to the occurrence of parenchymal hematoma (PH) formation on the 24-hour MRI scan using logistic regression. RESULTS: Signals indicating reversible BBB permeability were detected in 18/36 patients. Change in average BBB permeability correlated inversely with percent reperfusion (p=0.006), indicating that early reperfusion is associated with decreased BBB permeability while sustained ischemia is associated with increased BBB disruption. Focal regions of maximal BBB permeability were significantly associated with subsequent formation of PH (p=0.013). CONCLUSIONS: This study demonstrates that diffuse, mild BBB disruption in the acutely ischemic human brain is reversible with reperfusion. This study also confirms prior findings that focal severe BBB disruption confers an increased risk of hemorrhagic transformation in patients treated with IV tPA.